Allamanda alagoana (Apocynaceae), a remarkable new species from Northeastern Brazil - Alves-Silva, Jarina Waléria; Coutinho, Thales Silva (Phytotaxa, 2023)
Allamanda alagoana, a remarkable new species with muricate capsules, a unique character in the genus, is hereby proposed and described. The new species is endemic to the state of Alagoas, Brazil, and is known from a few collections from the Atlantic Forest domain. We provide a complete description, photographs, an illustration, a distribution map, conservation status, a table with diagnostic characters, and an identification key for the species of Allamanda found in the state of Alagoas.